2021
DOI: 10.1161/circulationaha.120.046462
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibition Reverses Preexisting Diastolic Dysfunction and Blocks Covert Extracellular Matrix Remodeling

Abstract: Background: Diastolic dysfunction (DD) is associated with the development of heart failure (HF) and contributes to the pathogenesis of other cardiac maladies, including atrial fibrillation (AF). Inhibition of histone deacetylases (HDACs) has been shown to prevent DD by enhancing myofibril relaxation. Here, we addressed the therapeutic potential of HDAC inhibition in a model of established DD with preserved ejection fraction (EF). Methods: Four weeks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 51 publications
5
62
4
1
Order By: Relevance
“…More recently, it was shown that pan-HDAC inhibition with the clinical-stage compound ITF2357/givinostat improved cardiac relaxation in murine models of hypertension- or aging-induced DD with preserved ejection fraction, and that SAHA was efficacious in a feline model of HFpEF due to slow, progressive ascending aortic banding ( 107 109 ). Surprisingly, in the murine models of DD, cardiac fibrosis was not observed by standard histological readouts, such as Picrosirius red staining ( 107 , 108 ), and improved diastolic function upon HDAC inhibition was attributed exclusively to augmented myofibril relaxation ( 107 ). However, further evaluation of hearts of mice with DD revealed “hidden fibrosis,” a process in which increased ECM deposition and remodeling were not detected by standard histological methods, but were uncovered by quantitative mass spectrometry and atomic force microscopy (AFM).…”
Section: Targeting Epigenetics As An Antifibrotic Therapeutic Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, it was shown that pan-HDAC inhibition with the clinical-stage compound ITF2357/givinostat improved cardiac relaxation in murine models of hypertension- or aging-induced DD with preserved ejection fraction, and that SAHA was efficacious in a feline model of HFpEF due to slow, progressive ascending aortic banding ( 107 109 ). Surprisingly, in the murine models of DD, cardiac fibrosis was not observed by standard histological readouts, such as Picrosirius red staining ( 107 , 108 ), and improved diastolic function upon HDAC inhibition was attributed exclusively to augmented myofibril relaxation ( 107 ). However, further evaluation of hearts of mice with DD revealed “hidden fibrosis,” a process in which increased ECM deposition and remodeling were not detected by standard histological methods, but were uncovered by quantitative mass spectrometry and atomic force microscopy (AFM).…”
Section: Targeting Epigenetics As An Antifibrotic Therapeutic Approachmentioning
confidence: 99%
“…However, further evaluation of hearts of mice with DD revealed “hidden fibrosis,” a process in which increased ECM deposition and remodeling were not detected by standard histological methods, but were uncovered by quantitative mass spectrometry and atomic force microscopy (AFM). This covert type of cardiac fibrosis was profoundly inhibited by ITF2357/givinostat in a manner that correlated with improved diastolic function ( 108 ), implicating HDAC inhibition as a potential therapeutic strategy to combat HFpEF induced by pathological ECM remodeling and resulting ventricular stiffening.…”
Section: Targeting Epigenetics As An Antifibrotic Therapeutic Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-clinical models of diastolic dysfunction are associated with alterations in left ventricular stiffness on atomic force microscopy that occur at the level of the cardiomyocyte sarcomere as well as due to extracellular matrix protein expansion 9 . Such tissue level changes can be assessed at macroscopic scale in human populations through analysis of diastolic mechanics.…”
Section: Mainmentioning
confidence: 99%